Die AGS-lidmaat se rolverwagtinge van sy/haar pastor: ’n beskrywende ondersoek - Putter, APJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2009)
AFS members' role expectations of the pastor: a descriptive investigation In this article, the focus will be on the findings of a qualitative research investigation (Putter 2006) of the role expectations of the AFM pastor and a literature study of theological training. It will probably show how joint progress towards components for continued theological training can be made. Training for the Apostolic Faith Mission (AFM) pastor for admission to the ministry varies from a one-year certificate to an honours degree in Theology, offered at various institutions. During the General Business Meeting of the AFM in 2008, constitutional amendments were approved that pave the way for having only one institution for theological training in the church. The new theological institution faces a major challenge, namely that of establishing relevant theological training, in order to avert the danger of being identified as an elitist, irrelevant work group, with its own pastor’s language that is understood only by a small group of insiders.